Effects of manipulating slowpoke calcium-dependent potassium channel expression on rhythmic locomotor activity in Drosophila larvae - McKiernan, Erin C. (PeerJ, 2013)
Rhythmic motor behaviors are generated by networks of neurons. The sequence and timing of muscle contractions depends on both synaptic connections between neurons and the neurons’ intrinsic properties. In particular, motor neuron ion currents may contribute significantly to motor output. Large conductance Ca2+-dependent K+ (BK) currents play a role in action potential repolarization, interspike interval, repetitive and burst firing, burst termination and interburst interval in neurons. Mutations in slowpoke (slo) genes encoding BK channels result in motor disturbances. This study examined the effects of manipulating slo channel expression on rhythmic motor activity using Drosophila larva as a model system. Dual intracellular recordings from adjacent body wall muscles were made during spontaneous crawling-related activity in larvae expressing a slo mutation or a slo RNA interference construct. The incidence and duration of rhythmic activity in slo mutants were similar to wild-type control animals, while the timing of the motor pattern was altered. slo mutants showed decreased burst durations, cycle durations, and quiescence intervals, and increased duty cycles, relative to wild-type. Expressing slo RNAi in identified motor neurons phenocopied many of the effects observed in the mutant, including decreases in quiescence interval and cycle duration. Overall, these results show that altering slo expression in the whole larva, and specifically in motor neurons, changes the frequency of crawling activity. These results suggest an important role for motor neuron intrinsic properties in shaping the timing of motor output.
Keywords: Ion channels; Slowpoke; Calcium-dependent potassium channels; Motor pattern; Locomotion; Intrinsic properties; Motor neurons; Drosophila